2015
DOI: 10.1186/s13054-015-1033-3
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilisation in intensive care units in Australia and Scotland: a prospective, observational cohort study examining mobilisation practises and barriers

Abstract: IntroductionMobilisation of patients in the intensive care unit (ICU) is an area of growing research. Currently, there is little data on baseline mobilisation practises and the barriers to them for patients of all admission diagnoses.MethodsThe objectives of the study were to (1) quantify and benchmark baseline levels of mobilisation in Australian and Scottish ICUs, (2) compare mobilisation practises between Australian and Scottish ICUs and (3) identify barriers to mobilisation in Australian and Scottish ICUs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 33 publications
7
107
1
12
Order By: Relevance
“…Few centres achieve Hodgson's definition of early mobilisation within 2-5 days10 16 27. Our QI project has enabled patients to mobilise out of bed within the first five days of their intensive care stay and to be discharged earlier from the ICU.…”
Section: Resultsmentioning
confidence: 99%
“…Few centres achieve Hodgson's definition of early mobilisation within 2-5 days10 16 27. Our QI project has enabled patients to mobilise out of bed within the first five days of their intensive care stay and to be discharged earlier from the ICU.…”
Section: Resultsmentioning
confidence: 99%
“…Prospectively defined and empirically evaluated barriers, as previously defined, were found in 17 studies (9,11,(13)(14)(15)(16)19,(23)(24)(25)(27)(28)(29)34,35,41,50), perceived barriers in 19 studies (12,(20)(21)(22)26,(31)(32)(33)(36)(37)(38)(39)(43)(44)(45)(46)(47)(48)(49) and a mix of both in 4 studies (10,30,40,42) (Table E1). Only 1 study used a validated instrument for the assessment of barriers (37), while other studies identified barriers using a variety of techniques, including interdisciplinary meetings (10,12,21,30,42) and interviews or custom-made surveys with clinicians…”
Section: Barriers and Strategiesmentioning
confidence: 91%
“…Interprofessional meetings † *; PT screening of ICU patients † * 32,41,42,46 Hemodynamic instability, arrhythmias Stepwise approach † ‡ *; protocols † ‡ *; safety criteria † ‡ *; avoid mobilization until 2 hours after increase in vasopressor dose † *, valid assessment † ‡ * 9,10,19,23,24,26,31,44,46,48,50 Respiratory instability/distress, ventilator asynchrony…”
Section: Physical Barriersmentioning
confidence: 99%
“…Indeed, the data segments presented in this study highlight the value of qualitative oriented research in eliciting clinicians' difficulties in everyday clinical practice, even when using diagnostic instruments deemed as valid and reliable through quantitative studies. They also suggest that such instruments need to be regularly revisited, especially in view of the trend towards less sedation and earlier mobilization in ICUs in various countries (Harrold et al, 2015;Leong et al, 2017). Nydahl et al (2018) also recruited a combination of nurses and doctors (n = 559) through snowball sampling in a study about delirium, but in their case sought to investigate delirium management practices in critical care units in German-speaking countries in Europe.…”
Section: What's In This Issuementioning
confidence: 99%